Quality Evaluation of Some Selected Commercially Imported Honey Available in Libyan Markets - Ismail Ajaj,; Kalthoum Awn,; Khalleefah, Wafa; Mahasn Kubbat,; Hanan Mosbah,; Huda Jelani, (AlQalam Journal of Medical and Applied Sciences, 2025)
The present work was conducted to evaluate the quality of ten brands of honey commercially available in the Libyan market. The moisture, color intensity, ash content, pH, and hydroxymethylfurfural (HMF) content were detected according to AOAC 1990-Official Methods and reference methods. The results were compared with Libyan Standard Legislation and the FAO's international standards.The results indicate that the color intensity of the honey samples varied, ranging from water white to dark amber. The study found that Australian honey in the UAE had the highest pH value, while floral honey from France exhibited the lowest. The moisture content ranged from 4.42% to 16.87%, and the ash content varied between 0.0037% and 0.287%. The results also indicated that the Spanish honey recorded the highest HMF value at 177.39 and 151.26 mg/kg, whereas Australian honey packed in the UAE had the lowest HMF value at 1.81 mg/kg. Some samples exceeded both FAO's international standards and Libyan standards. تم إجراء هذا البحث لتقييم جودة عشر علامات تجارية من العسل المتوفر تجارياً في السوق الليبية, حيث تم قياس الرطوبة وكثافة اللون ومحتوى الرماد ودرجة الحموضة ومحتوى هيدروكسي ميثيل الفورفورال وفقاً للطرق الرسمية لمنظمة1990 AOAC والطرق المرجعية. وقد تمت مقارنة النتائج مع المواصفات الليبية القياسية والمعايير الدولية لمنظمة الأغذية والزراعة. تشير النتائج إلى أن كثافة اللون في عينات العسل كانت متفاوتة، حيث تراوحت بين الأبيض المائي والعنبر الداكن. ووجدت الدراسة أن العسل الأسترالي المعبأ في دولة الإمارات العربية المتحدة كان له أعلى قيمة للأس الهيدروجيني في حين أظهر العسل الزهري من فرنسا أدنى قيمة. كما تراوحت نسبة الرطوبةفي العينات ما بين 4.42% و16.87%، أما محتوى الرماد فقد كان ما بين 0.0037% و0.287%. و أشارت النتائج أيضاً إلى أن العسل الإسباني سجل أعلى قيمة لنسبة الهيدروكسي ميثيل الفورفورال عند 177.39 و151.26 ملغم/كغم، بينما سجل العسل الأسترالي المعبأ في الإمارات العربية المتحدة أقل قيمة عند 1.81 ملغم/كغم. بذلك تكون معظم العينات قد تجاوزت كلاً من المعايير الدولية لمنظمة الأغذية والزراعة والمعايير الليبية